Fraud Pentagon in The Act of Cheating Financial Statements With The M-Score Method - Adi Susilo; Endang Masitoh; Suhendro Suhendro (Jambura Science of Management, 2021)
Fraudulent financial statements include a number of ways of doing, to benefit from others by mis-presenting material in financial statements. The purpose of this research is to test and lysis influence pressure, opportunity, rationalization, competence, and arrogance on the financial statements of transportation, toll roads, airports and ports listed on the Indonesia Stock Exchange (IDX) period 2015-2018, with a sample count of 52 where data collection is carried out by purposive sampling method. This type of quantitative research with case studies, data analysis method uses logistics regression analysis with spss program version 17. The results showed arrogance had an effect on financial report fraud while variable pressure, opportunity, rationalization, and competence had no effect on financial report fraud. Further research can increase the number of research samples so that the results of the research can represent all service companies.